Château Rouge: a "Little Africa" in Paris? - (:unkn) unknown (My University, 2013)
The Chateau Rouge area of Paris is regarded as an "African neighbourhood". But what is the reality behind this image? Marie Chabrol shows that it has less to do with residents' backgrounds than with the commercial uses of the area, which put this district at the heart of large-scale mobilities. Paris, like any major metropolis, has different neighbourhoods whose images are built and rebuilt around business activities linked to immigration. The Château Rouge area-situated in the shadow of Sacré-Coeur at the foot of the eastern slopes of Montmartre, in the 18 th arrondissement (city district) 1 of Paris-is often viewed as an "African neighbourhood". Although there are many foreign citizens from Sub-Saharan Africa and North Africa among its inhabitants (as in other areas of northern and eastern Paris 2), their presence alone does not explain the extraordinary numbers of Africans that frequent this neighbourhood. Rather, it is the number of specialist shops that creates an "African centrality" at the metropolitan level: the specificity of the products sold polarises the consumption practices of people of African or Caribbean origin, the vast majority of whom do not live here but give the area its image. Who are these "Africans of Château Rouge"? And how does this "migrant" or "minority" 3 commercial centrality, so typical of major world cities, function? A detailed study combining observations and a questionnaire-based survey 4 shows the diversity of users and practices in Château Rouge and reveals urban dynamics that are not immediately obvious. The extraordinary density of business activities in the neighbourhood masks large-scale daily mobility flows that connect it to other residential and commercial spaces, and which extend beyond the metropolitan area. Accordingly, a study of these mobilities is necessary in order to understand how neighbourhoods that are all too often apprehended only at local level actually
Keywords: African Research